(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the use of a soil cushion as a foundation system in cases where the underlying natural soils are susceptible to shrinkage. The study focuses on determining the optimal thickness of the soil cushion and evaluating the design resistance of the natural soil beneath it.